Promoting Women's Access to Economic Opportunities : Albania - World Bank Group (Washington, DC: World Bank, 2018)
Prospects for faster, more sustainable economic growth and higher living standards in Albania rely on increasing employment opportunities for all. By maintaining the current structure of labor participation, Albania is not capitalizing on its educated young population, as less than half (45.5 percent) of 15-64-year-old women are actively contributing to the economy through employment. Closing gender gaps in access to economic opportunities requires removing the existing barriers and disincentives to employment and entrepreneurship for women. Needed steps include: (i) improving access to assets and productive inputs, (ii) providing access to child- and eldercare, (iii) eliminating disincentives and barriers embedded in labor taxation and regulation, and (iv) increasing the employability of women through effective active labor market policies and adequate skills and training. Cross-cutting policies around social norms and discrimination, better access to information, and improved monitoring and evaluation systems are also important.